2013
DOI: 10.1371/journal.pone.0068368
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Domain Cassette 8 Plasmodium falciparum Erythrocyte Membrane Protein 1 Is Associated with Cerebral Malaria in Benin

Abstract: Background Plasmodium falciparum erythrocyte membrane protein-1 (PfEMP-1) is a highly polymorphic adherence receptor expressed on the surface of infected erythrocytes. Based on sequence homology PfEMP-1 variants have been grouped into three major groups A-C, the highly conserved VAR2CSA variants, and semi-conserved types defined by tandem runs of specific domains (“domain cassettes” (DC)). The PfEMP-1 type expressed determines the adherence phenotype, and is associated with clinical outcome of infection.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
60
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 29 publications
9
60
1
Order By: Relevance
“…In line with previously reported observations (25,26,39), DC8 and group A PfEMP1 were highly expressed in most hospitalized children, and the abundance of transcripts encoding DC8 PfEMP1 was statistically significantly higher in patients with severe malaria than in those with uncomplicated disease. In contrast to data from previous reports, the difference in the abundances of transcripts encoding DC13 (containing CIDR␣1.4) in patients with severe malaria or uncomplicated disease did not reach statistical significance.…”
Section: Figsupporting
confidence: 92%
See 3 more Smart Citations
“…In line with previously reported observations (25,26,39), DC8 and group A PfEMP1 were highly expressed in most hospitalized children, and the abundance of transcripts encoding DC8 PfEMP1 was statistically significantly higher in patients with severe malaria than in those with uncomplicated disease. In contrast to data from previous reports, the difference in the abundances of transcripts encoding DC13 (containing CIDR␣1.4) in patients with severe malaria or uncomplicated disease did not reach statistical significance.…”
Section: Figsupporting
confidence: 92%
“…Data from this study in combination with previously reported observations from other studies of var transcription (25,26,29,31) suggest that the expression of EPCR-binding PfEMP1 is the overarching parasite phenotype associated with the development of symptomatic and severe malaria and that its clinical relevance is stable across various confounding host or environmental factors. In line with this are the observations that parasites from children with severe disease and in vitro-adapted parasites expressing CIDR␣1 PfEMP1 bind endothelial cells via EPCR (22,(52)(53)(54) and that CIDR␣1 domains bind EPCR with high affinity, and binding inhibits the ability of EPCR to bind protein C, thereby potentially driving pathogenic endothelial inflammation (27,28,(55)(56)(57).…”
Section: Figsupporting
confidence: 74%
See 2 more Smart Citations
“…If this is true, it should be possible to protect children against severe malaria by inducing cross-reactive IgG by vaccination of infants. Analyses of var gene transcription and PfEMP1 expression in children suffering from severe malaria has indicated that parasites causing severe disease express a group of PfEMP1s binding endothelial protein C receptor (EPCR) (24)(25)(26)(27)(28). The binding is mediated by N-terminal CIDR domains, and only PfEMP1s containing CIDR domains of the subtypes ␣1.1 or ␣1.4 to ␣1.8 bind EPCR (29).…”
mentioning
confidence: 99%